A Radio Jet Drives a Molecular and Atomic Gas Outflow in Multiple Regions within One Square Kiloparsec of the Nucleus of the nearby Galaxy IC5063 - Dasyra, K. M.; Bostrom, A. C.; Combes, F.; Vlahakis, N. (IOP, 2015)
We analyzed near-infrared data of the nearby galaxy IC5063 taken with the Very Large Telescope SINFONI instrument. IC5063 is an elliptical galaxy that has a radio jet nearly aligned with the major axis of a gas disk in its center. The data reveal multiple signatures of molecular and atomic gas that has been kinematically distorted by the passage of the jet plasma or cocoon within an area of ∼1 kpc2. Concrete evidence that the interaction of the jet with the gas causes the gas to accelerate comes from the detection of outflows in four different regions along the jet trail: near the two radio lobes, between the radio emission tip and the optical narrow-line-region cone, and at a region with diffuse 17.8 GHz emission midway between the nucleus and the north radio lobe. The outflow in the latter region is biconical, centered 240 pc away from the nucleus, and oriented perpendicularly to the jet trail. The diffuse emission that is observed as a result of the gas entrainment or scattering unfolds around the trail and away from the nucleus with increasing velocity. It overall extends for ≳700 pc parallel and perpendicular to the trail. Near the outflow starting points, the gas has a velocity excess of 600-1200 km s-1 with respect to ordered motions, as seen in [Fe ii], Paα , or {H}2 lines. High {H}2 (1-0) S(3)/S(1) flux ratios indicate non-thermal excitation of gas in the diffuse outflow.
Keywords: Astrophysics - Astrophysics of Galaxies; galaxies: active; galaxies: ISM; galaxies: jets; galaxies: nuclei; ISM: jets and outflows; ISM: kinematics and dynamics